Developing algorithm for estimating chlorophyll-a concentration in the Thac Ba Reservoir surface water using Landsat 8 Imagery - Vinh, Pham Quang; Ha, Nguyen Thi Thu; Binh, Nguyen Thanh; Thang, Nguyen Ngoc; Oanh, La Thi; Thao, Nguyen Thien Phuong (Vietnam Journal of Earth Sciences, 2019)
This study aims at developing a regional algorithm to quantify chlorophyll-a concentration (Chla) in the Thac Ba Reservoir surface-water using Landsat 8 imagery basing on in-situ data of Chla and above-water reflectance taken in both dry and rainy seasons 2018. In situ datasets obtained from 30 water sampling sites show a strong correlation (R2=0.73) with the reflectance ratio of two Landsat 8 (L8) bands, the green band (band 3: B3) versus the red band (band 4: B4), B3 / B4, by an exponential equation. The algorithm for estimating Chla using this ratio was well-matched up the validation using multiple-dates in-situ datasets (R2 = 0.82; RMSE ~ 5%) and was then applied to L8 images level 2 acquired in both dry and rainy seasons to understand the spatiotemporal distribution of Chla over the reservoir. Obtained maps of Chla present clearly two trends: (1) Chla in the reservoir water in the dry season (averaged at 15.3 mg/m3) is relatively lower than those in the rainy season (averaged at 17.0 mg/m3); (2) In both seasons, Chla increased from water area in front of the Chay River mouth to the center of the reservoir. The algorithm and method outlined in this study could be applied to monitoring Chl in other inland waters having similar features as the Thac Ba Reservoir water.ReferencesAPHA, 1998. Standard Methods for the Examination of Water and Wastewater, 20th edition. American Public Health Association, Washington DC, 1220p.Bac N.A., Viet N.D., Ha N.T.T., Huong H.T.T., 2017. Identifying eutrophication status of shallow waters based on estimated trophic state index from satellite data. Journal of Science and Technology, 55(4C), 85-89.Bernardo N., Watanabe F., Rodrigues T., Alcântara E., 2017. Atmospheric correction issues for retrieving total suspended matter concentrations in inland waters using OLI/Landsat-8 image. Advances in Space Research, 59(9), 2335-2348.Boucher J., Weathers K.C., Norouzi H., Steele B., 2018. Assessing the effectiveness of Landsat 8 chlorophyll a retrieval algorithms for regional freshwater monitoring. Ecological Applications, 28(4), 1044-1054.Carlson R.E., 1977. A trophic state index for lakes1. Limnology and oceanography, 22(2), 361-369.Carlson R.E., Simpson J., 1996. A coordinator’s guide to volunteer lake monitoring methods. North American Lake Management Society, 96, 305.DWR - Directorate of Water Resource, 2017. Report on weather conditions, water supplies, flood control and irrigations security No. 49/BC-TCTL-QLCT to Minister of Agriculture and Rural Development (in Vietnamese) on October 16th, Hanoi, Vietnam. Gholizadeh M.H., Melesse A.M., Reddi L., 2016. A comprehensive review on water quality parameters estimation using remote sensing techniques. Sensors, 16(8), 1298.Gitelson A., Stark R., Oron G., Dor I., 1997. Monitoring of polluted water bodies by remote sensing. IAHS Publications-Series of Proceedings and Reports-Intern Assoc Hydrological Sciences, 242, 181-188.Ha N.T.T., Koike K., 2011. Integrating satellite imagery and geostatistics of point samples for monitoring spatio-temporal changes of total suspended solids in bay waters: application to Tien Yen Bay (Northern Vietnam). Frontiers of Earth Science, 5(3), 305.Kutser T., 2009. Passive optical remote sensing of cyanobacteria and other intense phytoplankton blooms in coastal and inland waters. International Journal of Remote Sensing, 30(17), 4401-4425.Kutser T., 2012. The possibility of using the Landsat image archive for monitoring long time trends in coloured dissolved organic matter concentration in lake waters. Remote Sensing of Environment, 123, 334-338.Michelutti N., Blais J.M., Cumming B.F., Paterson A.M., Rühland K., Wolfe A.P., Smol J.P., 2010. Do spectrally inferred determinations of chlorophyll a reflect trends in lake trophic status?. Journal of Paleolimnology, 43(2), 205-217.Mobley C.D., 1999. Estimation of the remote-sensing reflectance from above-surface measurements. Applied Optics, 38(36), 7442-7455.Nhung P.T., Canh B.D., Ha N.T.T., Linh N.T., 2016. Modeling spatial-temporal distribution of total suspended solids concentrations in Day Estuary water using Landsat 8 Imagery. Proceeding of the 7th International Symposium Hanoi Geoengineering 2016 on Energy and Sustainability, Hanoi, October 21-22, 69-75.Olmanson L.G., Bauer M.E., Brezonik P.L., 2008. A 20-year Landsat water clarity census of Minnesota's 10,000 lakes. Remote Sensing of Environment, 112(11), 4086-4097.Padisák J., Borics G., Grigorszky I., Soroczki-Pinter E., 2006. Use of phytoplankton assemblages for monitoring ecological status of lakes within the Water Framework Directive: the assemblage index. Hydrobiologia, 553(1), 1-14.Palmer S.C., Kutser T., Hunter P.D., 2015. Remote sensing of inland waters: Challenges, progress and future directions. Remote Sens. of Environ. Special Issue: Remote Sensing of Inland Waters, 157(1), 1-8.Quang N.H., Sasaki J., Higa H., Huan N.H., 2017. Spatiotemporal Variation of Turbidity Based on Landsat 8 OLI in Cam Ranh Bay and Thuy Trieu Lagoon, Vietnam. Water, 9(8), 570.Son N.H., Anh B.T, Thuy N.T.T, 2000. Investigation of the Fisheries in Farmer-Managed Small Reservoir in Thai Nguyen and Yen Bai Province. Proceedings of an International Workshop on Reservoir and Culture-based Fisheries: Biology and Management. Bangkok, Thailand 15-18 February, 246-257.Tebbs E.J., Remedios J.J., Harper D.M., 2013. Remote sensing of chlorophyll-a as a measure of cyanobacterial biomass in Lake Bogoria, a hypertrophic, saline-alkaline, flamingo lake, using Landsat ETM+. Remote Sensing of Environment, 135, 92-106.Thuy D.B., Canh B.D., Ha N.T.T., Thao N.T.P., Nhi B.T., 2016. Modeling spatial distribution of total suspended solids concentration in Ha Long Bay water during the first quarter of 2016 using co-kriging interpolation and auxiliary data from Landsat 8 imagery. Proceeding of the 7th International Symposium Hanoi Geoengineering 2016 on Energy and Sustainability, Hanoi, October 21-22, 148-153.Tiwari S.P., Shanmugam P., Ahn Y.H., Ryu J.H., 2012. A Reflectance Model for Relatively Clear and Turbid Waters. Engineering, Technology & Applied Science Research, 3(1), 325-337.UNEP, 2014. Review of existing water quality guidelines for freshwater ecosystems and application of water quality guidelines on basin level to protect ecosystems. Technical background document for theme 1: “Water Quality and Ecosystem Health”. First International Environment Forum for Basin Organizations towards Sustainable Freshwater Governance, 26-28 November 2014, Nairobi, Kenya.US Environmental Protection Agency, 2009. National lakes assessment: a collaborative survey of the nation's lakes, 103p.Vermote E., Justice C., Claverie M., Franch B., 2016. Preliminary analysis of the performance of the Landsat 8/OLI land surface reflectance product. Remote Sensing of Environment, 185, 46-56.Watanabe F., Alcantara E., Rodrigues T., Rotta L., Bernardo N., Imai N., 2018. Remote sensing of the chlorophyll-a based on OLI/Landsat-8 and MSI/Sentinel-2A (Barra Bonita reservoir, Brazil). Anais da Academia Brasileira de Ciências, 90(2), 1987-2000.Yang Z., Anderson Y., 2016. Estimating chlorophyll-a concentration in a freshwater lake using Landsat 8 Imagery. J. Environ. Earth Sci., 6(4), 134-142.